Functional specialization for judge of grievances in Islamic Law, Jordanian Law and Saudi Law - M. Bani Younes, Abed Al Salam Isaa; El-Seoudi, Abdel Wadoud Moustafa Moursi; Muhammad Husni, Ahmad (American-Eurasian Network for Scientific Information (AENSI Publisher), 2012)
This article compares and discusses the Functional specialization for judge of grievances at the Fifth century AH (at the Abbasi era) with the Functional specialization for judge of grievances in Jordanian Law and Saudi Law in current era. It searches for the extent to which the Jordanian and Saudi Laws achieves the same role which was achieved and applied in Abbasi era in this regard. This study is selected because of its importance in our life whereas any maltreated person should know the functional specialization for judge of grievances and, accordingly, know when he can resort to this judicature instead of the normal judicature. This study depends on qualitative methodology where the viewpoints of jurists are collected and the legitimate bases on which their opinions are built. It depends also on analytic methodology by analyzingthe legal articles and the collected viewpoints. Besides that, the study depends on quantitative approach by referring to grievances courts, search in the files and doing Interviews with the specialized persons. The conclusion of this study is that the functional specializations for judge of grievances in the Abbasi era were wider and more comprehensive than those in Jordanian and Saudi Laws. Also, the Abbasi judge had position and status stronger than the position and the status of the current judge in Saudi Arabia and Jordan.